2012
DOI: 10.4238/2012.may.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of alterations in the MEFV gene and clinical signs in familial Mediterranean fever in Central Anatolia, Turkey

Abstract: ABSTRACT. Familial Mediterranean fever is a recessive autoinflammatory disease that is frequent in Armenians, Jews, Arabs, and Turks. The MEFV gene is responsible for this disease. We looked for MEFV gene variations (polymorphism and mutations) in a population that resides in Central Anatolia, Turkey. DNA was extracted from peripheral blood leukocytes of 802 familial Mediterranean fever patients. The DNA sequence data were examined for approximately 150 different mutations and polymorphisms, including single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In agreement with our study, it was found as the second most commonly seen mutation in many studies from Turkey (Akin et al, 2010;Dogan et al, 2012;Etem, 2010;Gulec et al, 2012;Ozturk et al, 2008;Pasa et al, 2008;Solak et al, 2008;Ulgenalp, 2009), whereas it was found as the most commonly seen mutation in the study by Evliyaoglu et al (2009) and by Yesilada et al (2012), with allele frequencies of 30.8% and 10.38%, respectively. E148Q mutation was the third most commonly observed mutation in the study by Ceylan et al (2012) and by Dundar et al (2011) with the allele frequencies of 4.42 and 5.15%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…In agreement with our study, it was found as the second most commonly seen mutation in many studies from Turkey (Akin et al, 2010;Dogan et al, 2012;Etem, 2010;Gulec et al, 2012;Ozturk et al, 2008;Pasa et al, 2008;Solak et al, 2008;Ulgenalp, 2009), whereas it was found as the most commonly seen mutation in the study by Evliyaoglu et al (2009) and by Yesilada et al (2012), with allele frequencies of 30.8% and 10.38%, respectively. E148Q mutation was the third most commonly observed mutation in the study by Ceylan et al (2012) and by Dundar et al (2011) with the allele frequencies of 4.42 and 5.15%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Although we reported one single heterozygous subject with K695R, five recent studies from a different region in Turkey reported a total of 33 subjects (Dundar et al, 2011;Ceylan et al, 2012;Ozdemir et al, 2011;Yesilada et al, 2012;Oztuzcu et al, 2014). In a recent study by Albayrak et al (2010), conducted on the subjects in our region, four symptomatic K695R mutations were reported.…”
Section: Demonstrated a Complete Exomementioning
confidence: 61%
“…One heterozygous asymptomatic subject was the mother of a symptomatic compound heterozygous subject. Giaglis et al (2007) and Ceylan et al (2012) reported only one symptomatic homozygous T267I form. L110P was described as a common symptomatic mutation in Japan, as is the case for M694I (Migita et al, 2012;Tomiyama et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations